Comparative genomic hybridisation as a supportive tool in diagnostic pathology. Issue 7 (1st July 2003) - Weiss, M M; Kuipers, E J; Meuwissen, S G M; van Diest, P J; Meijer, G A
Abstract : Aims: Patients with multiple tumour localisations pose a particular problem to the pathologist when the traditional combination of clinical data, morphology, and immunohistochemistry does not provide conclusive evidence to differentiate between metastasis or second primary, or does not identify the primary location in cases of metastases and two primary tumours. Because this is crucial to decide on further treatment, molecular techniques are increasingly being used as ancillary tools. Methods: The value of comparative genomic hybridisation (CGH) to differentiate between metastasis and second primary, or to identify the primary location in cases of metastases and two primary tumours was studied in seven patients. CGH is a cytogenetic technique that allows the analysis of genome wide amplifications, gains, and losses (deletions) in a tumour within a single experiment. The patterns of these chromosomal aberrations at the different tumour localisations were compared. Results: In all seven cases, CGH patterns of gains and losses supported the differentiation between metastasis and second primary, or the identification of the primary location in cases of metastases and two primary tumours. Conclusion: The results illustrate the diagnostic value of CGH in patients with multiple tumours.